The rival doesn't catch my eyes: In-group relevance modulates inhibitory control over anti-saccades. Issue 1 (16th March 2017) - Moradi, Zargol; Duta, Mihaela; Hewstone, Miles; Yankouskaya, Alla; Enock, Florence; Humphreys, Glyn W.
ABSTRACT: We examined the effects of in-group relevance on inhibitory control in anti-saccades. In Experiment 1, following a central coloured cue, football fans were instructed to look at the target on pro-saccade trials or its mirrored position on anti-saccade trials. The targets were badges of participants' favourite football team (in-group), its closest rival, or a non-local neutral team. Our results revealed no significant differences on pro-saccade trials for in- versus out-groups. However, on anti-saccade trials participants made more directional errors for the in-group badge compared to the badges of the neutral and rival teams. Moreover, the percentage of directional errors to in-group stimuli on anti-saccade trials was positively correlated with satisfaction toward the participant's own team. Experiment 2, with separate blocks of pro- and anti-saccade and simple stimuli replicated the results of Experiment 1. Experiment 3, was conducted to test the effects of familiarity on the performance in pro- and anti-saccade tasks using items with no group relevance. Our results revealed that familiarity of the items with no group relevance did not modulate inhibitory control in anti-saccade trials. Further, Experiment 4 showed that for participants who did not have any interest in football the performance in anti-saccades did not differ for different football teams. Overall, our findings suggest that under conditions of real-world intergroup rivalry in-group relevance modulates inhibitory control over anti-saccades. Future studies should seek to unravel the mechanisms contributing to the effects of group relevance on inhibitory control.